1982 Ultrasonics Symposium 1982
DOI: 10.1109/ultsym.1982.197843
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Ion Etching of Piezoelectric Films for Acoustic Wave Devices

Abstract: Iowa S t a t e U n i v e r s i t v Ames, Iowa A b s t r a c t R e a c t i v e I o n E t c h i n g ( R I E ) which combines some advantages o f b o t h plasma e t c h i n g and s p u t t e r e t c hi n g has been used i n p r o c e s s i n g ZnO/Si and A l N / S i s t r u c t u r e f o r a c o u s t i c wave d e v i c e s . In t h i s s t u d y , t h e e t c h i n g gases used a r e CF4, HC1 and HI w i t h v a r y i n g amounts o f 02 and A r . The s u b s t r a t e s o f i n t e r e s t , which a r e p l a c e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The experiment described here was developed considering discrepancies in past research (6) and the availability of ion implantation equipment (used in the experiment) to industry (7). Research conducted in the mid-1960s (8,9) has indicated that certain dopants could be ionimplanted into diamond, but the relative amounts of radiation damage and the apparently small amount of boron that was electrically active redirected most diamond research efforts toward other, more promising techniques (10,11).…”
Section: University Of Minnesota Assisted In Meeting the Publication ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment described here was developed considering discrepancies in past research (6) and the availability of ion implantation equipment (used in the experiment) to industry (7). Research conducted in the mid-1960s (8,9) has indicated that certain dopants could be ionimplanted into diamond, but the relative amounts of radiation damage and the apparently small amount of boron that was electrically active redirected most diamond research efforts toward other, more promising techniques (10,11).…”
Section: University Of Minnesota Assisted In Meeting the Publication ...mentioning
confidence: 99%
“…However, few successful attempts in dry etching of ZnO have been reported. Wang et al (6) used HBr and H1 to plasma etch ZnO, but the corrosive nature of HBr and H1 in most vacuum systems places practical limitations on delineation approaches using these gas mixtures (7).…”
mentioning
confidence: 99%